SEX-DEPENDENT HEAT TOLERANCE PROFILES OF BALI CATTLE EXPOSED TO TROPICAL HEAT STRESS - Kirana Dara Dinanti Adiputra; Sukandi; Karenina Dwi Yulianti; Nurliani Erni; Dani Nur Arifin (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Heat stress is one of the main challenges in livestock farming systems in tropical areas, directly affecting the physiological response and productivity of livestock. Bali cattle, as one of Indonesia's local germplasms, are known to have good adaptability to extreme environmental conditions. This study aims to evaluate the heat tolerance of male and female Bali cattle using the Iberian Heat Tolerance Coefficient (IHTC), Benezra’s Coefficient of Adaptability (BCA), and Thermal Stress Resistance Index (TSRI). Data analysis used the independent samples t-test to compare between male and female sexes under heat stress conditions (THI = 84.8–87.2). The results showed significant differences (P < 0.05) in IHTC and BCA values between male and female Bali cattle, while TSRI did not show significant differences (P > 0.05). Male Bali cattle had lower IHTC values and higher BCA values compared to female cattle. This finding indicates that female Bali cattle have relatively better heat tolerance compared to male Bali cattle.